2021
DOI: 10.1109/jsait.2021.3054598
|View full text |Cite
|
Sign up to set email alerts
|

Network Coding-Based Post-Quantum Cryptography

Abstract: We propose a novel hybrid universal network-coding cryptosystem (HUNCC) to obtain secure post-quantum cryptography at high communication rates. The secure network-coding scheme we offer is hybrid in the sense that it combines information-theory security with public-key cryptography. In addition, the scheme is general and can be applied to any communication network, and to any public-key cryptosystem. Our hybrid scheme is based on the information theoretic notion of individual secrecy, which traditionally relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…Authors have focused on implementing this approach and suggested improving the performance in implementation, applying standard model or quantum random oracle model to get better experiences. The hardness of distinguishing a code from pseudorandom code : Rank metrics play important role in various applications associated with code‐based cryptography. Few applications include space–time coding, network coding, and asymmetric key‐based cryptosystems 227–229 . Hardness is a theoretical property of a code.…”
Section: Quantum and Post‐quantum Cryptographymentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have focused on implementing this approach and suggested improving the performance in implementation, applying standard model or quantum random oracle model to get better experiences. The hardness of distinguishing a code from pseudorandom code : Rank metrics play important role in various applications associated with code‐based cryptography. Few applications include space–time coding, network coding, and asymmetric key‐based cryptosystems 227–229 . Hardness is a theoretical property of a code.…”
Section: Quantum and Post‐quantum Cryptographymentioning
confidence: 99%
“…The cryptosystems based on these schemes are well protected from various attacks with different coding schemes. However, the hardness of the rank metric is required to ensure security in various applications like post‐quantum cryptography security with network coding 227 . Bardet et al 222 discussed the algebraic attack on the rank metric in a code‐based cryptosystem.…”
Section: Quantum and Post‐quantum Cryptographymentioning
confidence: 99%
“…In order to improve the throughput, [5] introduced individual computational security. This notion is to computational security as individual security is to strong security.…”
Section: Security Throughput and Delaymentioning
confidence: 99%
“…A secure scheme, which obtains a trade-off between a postquantum security guarantee (for a strong Eve) and throughput, was presented in [5]. The scheme is called a hybrid universal network-coding cryptosystem (HUNCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation